Evaluation Review on Effectiveness and Security Performances of Text Steganography Technique - Roshidi Din; Sunariya Utama; Aida Mustapha (Institute of Advanced Engineering and Science, 2018)
Steganography is one of the categories in information hiding that is implemented to conceal the hidden message to ensure it cannot be recognized by human vision. This paper focuses on steganography implementation in text domain namely text steganography. Text steganography consists of two groups, which are word-rule based and feature-based techniques. This paper analysed these two categories of text steganography based on effectiveness and security evaluation because the effectiveness is critically important in order to determine that technique has the appropriate quality. Meanwhile, the security is important due to the intensity performance in securing the hidden message. The main goal of this paper is to review the evaluation of text steganography in terms of effectiveness and security that have been developed by previous research efforts. It is anticipated that this paper will identify the performance of text steganography based on effectiveness and security measurement.